Efektivitas Kinerja Part-Time terhadap Efisiensi Operasional UMKM, Daerah Gonilan - Marsshanda Kartika Sari; Tri Ratna Pamikatsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to review the perspectives of MSME owners in the Gonilan area, particularly regarding part-time workers and their use in improving operational cost efficiency. The Gonilan area is known to have many MSMEs operating in various sectors, making this study relevant for understanding the challenges they face. A qualitative method was chosen so that the researcher could conduct in-depth interviews with three MSME owners. The informants were selected because they employed both full-time and part-time workers. The interview results showed that part-time workers were effective in reducing operational costs, such as more flexible hourly wages, although there were some disadvantages. The main disadvantages of part-time workers included lack of experience and limited working hours, which could be overcome through extra training and clear task distribution so that they could focus and increase productivity. The study concluded that the use of part-time workers has a significant impact on the operational cost efficiency of MSMEs, helping owners navigate the market without excessive financial burdens and encouraging long-term business growth.